Obesity-associated macrophages dictate adipose stem cell ferroptosis and visceral fat dysfunction by propagating mitochondrial fragmentation - Yan Tao; Jinhao Zang; Tianci Wang; Peixuan Song; Zixin Zhou; Huijie Li; Yalin Wang; Yiyang Liu; Haipeng Jie; Mei Kuang; Hui Zhao; Fuwu Wang; et al. (Nature Communications)
Abstract Morbid obesity induces adipose stem cell (ASC) shortage that impairs visceral adipose tissue (VAT) homeostasis. Macrophages cooperate with ASCs to regulate VAT metabolism, their impact on ASC shortage remains elusive. TNF-α-induced protein 8-like 2 (TIPE2) is an important regulator in immune cells, its expression in VAT macrophages and function in macrophage-ASC crosstalk are largely unknown. Here, TIPE2 loss in VAT macrophages promotes ASC ferroptosis to aggravate diet-induced obesity and metabolic disorders in male mice, which can be corrected by macrophage-specific TIPE2 restoration in VAT. Mechanistically, TIPE2-deficient macrophages propagate mitochondrial fragmentation and reduce delivery of exosomal ferritin toward ASCs, resulting in mitochondrial ROS and Fe2+ overload that dictates ASC ferroptosis. TIPE2 interacts with IP3R to constrain IP3R-Ca2+-Drp1 axis, thereby preventing excessive mitochondrial fission and enabling macrophages to protect against ASC ferroptosis. This study reveals distinct obesity-associated macrophages that dictate ASC ferroptosis, and proposes macrophage TIPE2 as therapeutic target for obesity-related diseases.